2013
DOI: 10.1200/jco.2012.47.4007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Donor KIR2DL1 Allelic Polymorphism on the Outcome of Pediatric Allogeneic Hematopoietic Stem-Cell Transplantation

Abstract: A B S T R A C T PurposeKiller-cell immunoglobulin-like receptors (KIRs) that regulate natural-killer cells are highly polymorphic. Some KIR2DL1 alleles encode receptors that have stronger signaling function than others. We tested the hypothesis that the clinical outcomes of allogeneic hematopoietic stem-cell transplantation (HSCT) could be affected by donor KIR2DL1 polymorphism. Patients and MethodsAll 313 pediatric patients received allogeneic HSCT at a single institution. Donor KIR2DL1 functional allele typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 49 publications
2
49
0
1
Order By: Relevance
“…[1][2][3][4] The therapeutic effect of haplo-HSCT is largely dependent on the graft-versus-leukemia effect exerted by natural killer (NK) cells, which contribute to eradicate leukemia cells surviving the preparative regimen. [5][6][7][8] Unfortunately, in the haplo-HSCT setting performed through the infusion of positively selected CD34…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The therapeutic effect of haplo-HSCT is largely dependent on the graft-versus-leukemia effect exerted by natural killer (NK) cells, which contribute to eradicate leukemia cells surviving the preparative regimen. [5][6][7][8] Unfortunately, in the haplo-HSCT setting performed through the infusion of positively selected CD34…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of allele-specific expression in NK cells of healthy controls by flow cytometry revealed a significantly decreased expression of KIR2DL1*004, an allele that was previously shown to have impaired signaltransduction capacity (supplemental Table 3). 16 However, PCR-SSP subtyping for the most common alleles (covering .98% of KIR2DL1 allotypes in whites) 15 including KIR2DL1*004 did not reveal significant differences (Table 1 and supplemental Table 2). Similarly, no significant changes in frequency and CNV were found for the C2-specific stimulatory KIR2DS1 (Table 1 and supplemental Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…Notably, this assay requires less than 0.1 mg of DNA and can be performed within 1 day. Using this assay, investigations showed that patients who received a donor graft containing the stronger KIR allele had fewer relapses, better survival, and less transplant-related mortality (29). These effects were observed regardless of primary disease [acute myelogenous leukemia (AML) vs.…”
Section: Regulatory Receptorsmentioning
confidence: 91%